Pengaruh Provider 4G di Game Honor of Kings terhadap Performa Pemain dalam Mode (Custom, Visual Skin, dan Ranked) - Enrico Ananta Pratama; Djul Fikry Budiman; Made Sutha Yadnya (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to analyze the effect of internet service quality from three 4G providers (Telkomsel, XL, and Tri) on player performance in the Honor Of Kings game in three different modes, namely Custom, Skin Visualization, and Ranked. Measurements were made using Quality Of Service parameters such as throughput, packet loss, and delay with the help of Wireshark software and processed using statistical methods by calculating the average Quality Of Service parameters from each provider by playing the Honor Of Kings game in Custom, Skin Visualization, and Ranked modes. The average of the results showed that Telkomsel consistently recorded the best performance with the highest throughput (7.59 Kbps in custom mode, 7.27 Kbps in visual skin, and 6.84 Kbps in Ranked mode), the lowest packet loss (0.94%, 1.21%, and 1.43%), and the fastest delay (55 ms in Custom mode, 59 ms in Visual Skin, and 63 ms in Ranked mode). This study concludes that the choice of internet provider has a significant impact on the comfort and performance of playing online games, with Telkomsel as the optimal choice to support competitive and visual activities in Honor Of Kings. This finding can be a reference for players in choosing internet services that suit gameplay needs.